Finance and competitiveness in developing countries - Fanelli, José María; Medhora, Rohinton, 1959- (Routledge studies in development economics, 2002)
Using detailed trade and firm-level financial data, the authors demonstrate, for example, that while links between finance and competitiveness are strong, they are not uniform across sectors and countries. This book examines the link between finance and competitiveness at the macro and sectoral levels in seven different countries: Argentina, Brazil, India, Indonesia, the Philippines, South Africa, and Tunisia, and investigates key international issues, such as the evidence of the impact of exchange rate variability on trade, patterns in bank lending, and trade openness and development.